Pengaruh Kualitas Pelayanan Penyediaan Air Bersih Terhadap Kepuasan Pelanggan di PDAM Kabupaten Tapin - Noor Rezqi Kusuma; Rudy Haryanto (BIMA: Jurnal Bisnis dan Manajemen, 2023)
The purpose of the study was to determine whether service quality (tangible, realibility, responsiveness, assurance, emphaty) simultaneously affects PDAM Tapin customer satisfaction, and whether service quality (tangible, realibility, responsiveness, assurance, emphaty) has a partial effect on PDAM Tapin Regency customer satisfaction, and service quality (tangible, realibility, responsiveness, assurance, emphaty) The variables that have the most dominance in terms of influencing customer satisfaction of PDAM Tapin district. In this research method using quantitative research methods. The analytical methods used for this study are validity and reality tests, linear regression analysis, flatfoot assumption tests. From the results of this study: The independent variables of Service Quality (Tangible (X1), Realibility (X2), Responsiveness (X3), Assurance (X4), Emphaty (X5) have a significant simultaneous effect on customer satisfaction in PDAM Tapin Regency Company, 77.8% of the results have a residual, namely 22.2%, so this is influenced by other variables outside this study. The results of the Tangible Variable (X 1) did not have a partial significant effect on customer satisfaction at the PDAM Tapin Regency Company with a Tcalculate value of -1.149. Variable Realibility (X2) Does not have a significant partial effect on customer satisfaction at PDAM Tapin Regency Company with a Tcalculate value of 1,358. The Responsivenss variable (X3) has a significant partial effect on customer satisfaction at PDAM Tapin Regency Company with a Tcalculate value of 4,431.The Assurance variable (X4) has a significant partial effect on customer satisfaction at PDAM Tapin Regency Company with a Tcalculate value of 2,266. Emphaty variable (X5) does not have a partial significant effect on customer satisfaction at PDAM Tapin Regency Company with a Tcalculate value of 1.108. The variable with the most dominant influence is the Responsivenss variable on customer satisfaction in PDAM Tapin Regency companies with the largest r2 value is the Responsivenss variable which is 0.210 or 21%.